Pengaruh Rebranding Terhadap Brand Image Serta Kepuasan dan Loyalitas Pelanggan - Dojeng Meisi Koo; Desy Prastyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Since the end of the BreadTalk name license period in Indonesia, the franchisor decided to rebrand and change the BreadTalk name to Mako Cake and Bakery. This step was taken to maintain their market share. This is certainly quite risky because it can affect customer satisfaction and loyalty for the formation of a new brand image. Therefore, this study was conducted to see the effect of rebranding on brand image and customer satisfaction and loyalty at Mako. The population in this study consisted of BreadTalk customers in the Tangerang area. While the research sample was taken using purposive sampling technique with a total of 125 respondents. This research is a quantitative study using the Structural Equation Model - Partial Least Square (SEM-PLS) method. The results showed that rebranding has a positive effect on customer satisfaction, customer loyalty, and brand image. Then, brand image has a positive effect on customer satisfaction and loyalty. Finally, customer satisfaction has a positive effect on customer loyalty. After conducting the research, the authors suggest expanding the population to other major cities, in order to represent more BreadTalk customers in Indonesia for the rebranding that has been carried out. In addition, it can also add other supporting variables, such as service quality, product quality, product price, purchasing decisions, or other relevant variables as a research novelty. Keywords: rebranding, brand image, customer satisfaction, customer loyalty.